Współczesny stan badań nad prawosławną hagiologią - Charkiewicz, Jarosław (Elpis, 2014)
Hagiology is relatively young branch of theology. It deals with issues related to the study of holiness from theological perspective. The modern state of research on Orthodox hagiology in Poland is not advanced. The study on holiness in our country essentially boils down to the issues connected to the lives of saints. Therefore it is usually limited to the hagiography and is conducted more from literately than theological perspective. A bit more advanced study in the field of Orthodox hagiology than in Poland can be observed abroad. The researches in this area deal mainly by a few Russians, Greeks and Serbs. Some hope for the development of Orthodox hagiology can be associated with organized more frequently, mainly in Russia, in the beginning of this century, scientific conference on this subject. Favorable, although slow, changes can be seen also in the curricula of some universities of theology, where the subject named “hagiology” appeared recently.